HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN POWER OTOT LENGAN-BAHU DENGAN HASIL AKURASI SMASH BULUTANGKIS PUTRA PADA PB. ANGKASA PEKANBARU - Arisman Arisman; Saripin Saripin; 2Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is seen that their smash ability is still not good, the direction of cock flat and not dip, easy punch returned, the way the ball is not tight, the cock is often out of the field or does not lead to the target and also there is still a concern on the net. This matter allgedly doe to the lack of wrist and arm muscle power that is not good so that the smash accuracy does not lead to the target smash. The study aims to determine whether there is a correlation between the formation of the wrist and arm muscle power whit the result of the smash accuracy badminton son on PB. Angkasa Pekanbaru. Sampling technique that is the whole population (total sampling) badminton athlete PB. Angkasa son Pekanbaru numbered 8 people. This research uses correlation technique. Then, the test data using the normality test, product moment correlation test, and test that Lcalculate variable X1 = 0,254, Lcalculate variable X2 = 0,140 and Lcalculate variable Y = 0,190 where Ltable obtained 0,285 (α = 0,05), with So Lcalculate = 0,254 < L table 0,285 on variable X1, Lcount 0,140 < Ltable = 0,285 on the variable X2 and Larithmetic = 0,190 < Ltable = 0,285 on variable Y, in other words it is concluded that X1, X2 and Y data are distributed normal.Keywords: Wrist Flexibility, Arm Muscle Power, Smash Accuracy.